2017
DOI: 10.1242/jeb.154484
|View full text |Cite
|
Sign up to set email alerts
|

miR-210 expression is associated with methionine-induced differentiation of trout satellite cells

Abstract: In fish, data on microRNAs (miRNAs) involved in myogenesis are scarce. In order to identify miRNAs involved in satellite cell differentiation, we used a methionine depletion/replenishment protocol to synchronize myogenic cell differentiation. Our results validated that methionine removal (72 h) from the medium strongly decreased and expression, indicating differentiation arrest. In contrast, methionine replenishment rescued expression of and, showing a resumption of differentiation. We performed a miRNA array … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
(56 reference statements)
1
18
0
Order By: Relevance
“…Meanwhile, miRNAs are also known to participate in nutrient-regulated myogenesis. For instance, genistein, which is abundant in soybean, enhances myogenic differentiation by regulating miR-222 expression [ 26 ], methionine induces myogenic differentiation in trout using uses miR-210 [ 27 ], and dietary energy levels affect muscle fiber type transformation by changing miRNA expression [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, miRNAs are also known to participate in nutrient-regulated myogenesis. For instance, genistein, which is abundant in soybean, enhances myogenic differentiation by regulating miR-222 expression [ 26 ], methionine induces myogenic differentiation in trout using uses miR-210 [ 27 ], and dietary energy levels affect muscle fiber type transformation by changing miRNA expression [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The iron-sulfur cluster scaffold homolog and cytochrome c oxidase assembly protein genes, regulators of mitochondrial and tricarboxylic acid cycle function, have been reported as targets of miR-210 [ 38 ]. During the differentiation of satellite cells, the expression of miR-210 was upregulated, indicating the potential involvement of miR-210 in trout myogenesis [ 39 ]. Furthermore, the miR-210 expression level also increased during myogenic differentiation with a Hif1a-dependent mechanism in normoxia.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism that has emerged as a factor in MR phenotypes is microRNAs (miRNAs). Studies have shown that MR alters miRNA expression levels in rainbow trout myosatellite cells ( 4 , 5 ) and bone structures of mice ( 6 ), supporting a proposed connection between MR and miRNAs. This review will discuss the history and phenotypes associated with MR, as well as the role for miRNAs in MR phenotypes.…”
Section: Introductionmentioning
confidence: 85%
“…Recent evidence also supports a role for miRNAs in the MR phenotype in teleosts and mammals. Rainbow trout myosatellite cells exposed to methionine-deficient cell media regulate miRNAs that reduce their capacity for differentiation (miR-133a, miR-206, and miR-210) ( 4 ). Rainbow trout fed an MR (0.775%) diet for 4 weeks had lower levels of miR-133a in the skeletal muscle at 4 weeks and increased glucose tolerance following a glucose challenge at 8 weeks ( 5 ).…”
Section: Physiological Mechanisms Of Mrmentioning
confidence: 99%
See 1 more Smart Citation